IMPLEMENTASI PEMILIHAN KEPALA DESA DALAM KERANGKA DEMOKRASI LOKAL (STUDI KEGAGALAN PROSES PEMILIHAN KEPALA DESA DI DESA GEDANGAN KECAMATAN GROGOL KABUPATEN SUKOHARJO) - Syaranamual, Chintya Amelia; Achmad, Achmad (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This legal writing examines how the development process in the Gedangan village, Grogol sub-district, Sukoharjo district in the concept of local democracy. Second, how the impact of the failure of the process of conducting village head elections for village government and citizens of Gedangan Village.This research is using descriptive empirical research method and qualitative approach. Primary and secondary data sources are used in this study as types and data sources of the research. Data collection techniques that are used are interviews, observation, and literature study. Based on the research results, it shows that the failure of the Village Head election process in Gedangan Village was motivated by several factors. Firstly in the stage of the implementation of village head election 2016 Gedangan village community does not believe in the system of execution of additional selection and written tests at the district level because the implementation is not democratic and transparent so that people reject the results of additional selection and written tests at the district level. Second, the majority of the village head election committee resigned. Thirdly, the Village Consultative Body (BPD) in the deliberative meeting took the position to revoke the mandate of the Village Head committee so that the election of the Village Head ceased in the preparation stage.